Leitura de livros acadêmicos por docentes de língua portuguesa : escolha, relevância e aplicação - Mata, Luci Gomes da (2015)
The present research, linked to the Post-Graduate Education Program in Education (PPGEDU/CUR/UFMT) at the Federal University of Mato Grosso investigated the readings of effective Portuguese Language teachers of the state network in Rondonópolis, Mato Grosso. For this, it was used the content analysis method, in a quanti-qualitative approach, from structured questionnaires. In this sense, the research proposed, as a general objective to analyze what are the academic books read by the Portuguese Language teachers, identified as most relevant works, both for their formation, as for its operations in the mother tongue teaching. In this context and for this research, the relevant readings were the academic nature ones, carried out by Portuguese teachers as subsidies for their own formation and teaching practice. Therefore, the specific objectives are: Identify what are the academic books most read by the Portuguese Language teachers from the state network in Rondonópolis - Mato Grosso; Investigate the genres of academic books most read by Portuguese teachers during the year 2013 to April 2014; Investigate, from the perspective of teachers, what is the relevance of academic lectures in their own formation and educational activities. The data indicate interesting figures about Portuguese Language teachers reading: from twenty (20) state network schools were collected thirty (30) subjects testimonys which resulted in the information that will be presented. From the analyzed collection, (43%) were specific readings for own formation and teaching professional practice of Portuguese and (57%) referred to the reading of other genres. Responding to the first specific objective of the research, academic books referenced by subjects as the most widely read were Linguistics genre that depicts (47%) of the specific universe of the Portuguese Language area and (34%) Pedagogy gender, however, devoted to the study and teaching of Portuguese discipline. In all the academic content of the works cited as read is observed that they were divided into teacher formation lectures and readings for teaching the discipline of Portuguese Language, categorized into topics that discuss techniques and tips directed to the teacher. In the thematic reading area showed up the most, a total of thirteen (13) books. About the relevance of the readings assigned by teachers of Portuguese Language, which responds to the third specific objective, most teachers reported that all readings cited as performed by them are important to the performance and teacher formation.